A discourse analysis of english school announcements - Trương Lê Hồng Ngọc (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study is aimed at examining and finding the typical discourse features of school announcements in English in terms of their layout, lexical features, syntactic structures and cohesion and to suggest some implications for preparing an announcement to Vietnamese learners, especially English-majored students concerning the production of announcements in school. The study is carried out through qualitative and quantitative methods. Two hundred English samples of school announcements collected from TOEFL IBT books, universities in Great Britain, the U.S and Australia are analyzed. The results of the study are expected to give language teachers and learners a description of discourse features of English school announcement and help learners have a new look in preparing an announcement of their own in English